2009
DOI: 10.1029/2008pa001696
|View full text |Cite
|
Sign up to set email alerts
|

Glacial‐interglacial circulation changes inferred from 231Pa/230Th sedimentary record in the North Atlantic region

Abstract: [1] Studies from the subtropical western and eastern Atlantic Ocean, using the 231 Pa/ 230 Th ratio as a kinematic proxy for deep water circulation, provided compelling evidence for a strong link between climate and the rate of meridional overturning circulation (MOC) over the last deglaciation. In this study, we present a compilation of existing and new sedimentary Th ratio measured in upper Holocene sediments indicates slow water renewal above $2500 m and rapid flushing below, consistent with our unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
253
1
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(300 citation statements)
references
References 106 publications
36
253
1
10
Order By: Relevance
“…The finding of a limited reduction during HS1 suggests a greater sensitivity of climate change to variations in AMOC than previously modelled 8,9 , with important implications for regional and global climate. Both the reduction documented here for HS1 and the subsequent rapid increase in the rate of AMOC previously observed in 231 Pa/ 230 Th records at B15 ka 15,16,21 likely contributed to global deglaciation, the former by influencing the hemispheric temperature gradient and contributing to the rise in atmospheric CO 2 (refs 10,11,13) and the latter by adding enhanced meridional ocean heat transport to the warming effects of rising insolation and greenhouse gases and combining to accelerate the melting of northern ice sheets 10,12,16,19 . Supplementary Fig.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The finding of a limited reduction during HS1 suggests a greater sensitivity of climate change to variations in AMOC than previously modelled 8,9 , with important implications for regional and global climate. Both the reduction documented here for HS1 and the subsequent rapid increase in the rate of AMOC previously observed in 231 Pa/ 230 Th records at B15 ka 15,16,21 likely contributed to global deglaciation, the former by influencing the hemispheric temperature gradient and contributing to the rise in atmospheric CO 2 (refs 10,11,13) and the latter by adding enhanced meridional ocean heat transport to the warming effects of rising insolation and greenhouse gases and combining to accelerate the melting of northern ice sheets 10,12,16,19 . Supplementary Fig.…”
Section: Discussionmentioning
confidence: 79%
“…2b). The highest ratio, measured at 1.2 km in the NE Atlantic, is in an area characterized by high scavenging today 27 , while deeper cores show lower ratios 21,28,29 (Fig. 2b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McManus et al (2004) suggested a near total collapse of Atlantic MOC during Heinrich event 1 based on a sedimentary Pa/Th record from the Bermuda Rise. However, since the adsorbed sedimentary Pa/Th signal is also highly sensitive to particle compositions (biogenic silica content) such an interpretation has to be treated with caution and Atlantic MOC reduction may not have been so severe (Chase et al, 2002;Hall et al, 2006;Keigwin and Boyle, 2008;Gherardi et al, 2009;Lippold et al, 2009). In addition, several of the major Heinrich IRD discharge events (H1, H2, H4) were apparently accompanied by meltwater precursor events originating from the Northwest European Ice Sheet (NWEIS) suggesting that ice sheet collapse of European origin may have pre-conditioned the MOC in the North Atlantic (Peck et al, 2007b).…”
Section: Climate and Hydrographymentioning
confidence: 99%
“…There are two main ways of addressing the outstanding issues. The first is to continue to collect 231 Pa/ 230 Th down-core records covering a range of depths and locations with associated mineralogical and particle flux data [73]. Such an approach would give the mean 231 Pa/ 230 Th sedimentary ratio on a basin-wide scale, better suited to assessing the large-scale effect of particles on 231 Pa/ 230 Th and maximizing the potential for modelling studies to distinguish unique circulation patterns.…”
Section: (I) Salinity and Temperaturementioning
confidence: 99%